Airlangga University Student Depression Level During the COVID-19 Pandemic Based on Age and Gender - Rahmasari, Nadiyah; Dian Eka Sari, Jayanti; Rido’i Yuda Prayogi, Ahmad; Alamiyyah, Mirah; Indah Sari, Kurnia (Universitas Negeri Semarang, 2021)
The COVID-19 pandemic has caused teaching and learning activities to be carried out online. With this policy, students will easily experience depression due to limited space. This study aims to identify the age, gender, and level of depression of Airlangga University students and analyze the relationship between age and gender with the level of depression of Airlangga University students during the COVID-19 pandemic. This research is a quantitative study with a cross-sectional approach carried out in April - June 2020. The population in this study were Airlangga University students, with a sample of 386 students. The sampling technique used is non-probability sampling. The data collection method used a K10 questionnaire. The data analysis method used the chi-square test. This study showed that 61.1% of respondents were aged 20-21 years, 80.3% of respondents were female, and 51.6% of respondents did not experience depression. Furthermore, there was no significant relationship between age (p-value = 0.295 0.005) and gender with the level of depression (p-value = 0.415 0.005). It is hoped that this research can add to the public's views regarding depression levels in students during the COVID-19 pandemic in terms of gender and age.